Dialogues exchanged between Louis I. Kahn, Anne Tyng and Colin Rowe. Trenton Jewish Community Center - Martín Domínguez, Guiomar; Rodríguez Martín, Isabel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
The 1950s represent a major turning point in Louis Kahn’s career; a time in which his determination to comprehend Architecture’s quintessence led to the formulation of a series of decisive transformations in the conception of order and modernist space. His intuitions about the autonomous and indivisible condition of the ‘room’, based on the intimate agreement between the envelope and its structure, entwined with a simultaneous interest in the growth processes of forms, partly influenced by key figures in the North American context such as Buckminster Fuller and Robert Le Ricolais, and above all due to his intense collaboration with Anne Tyng. The evolution of the design for the Trenton Jewish Community Center can be regarded as paradigmatic of this junction of interests. Through it one can see how the transition from a ‘cellular’ layout of organic appearance to a regular chequered plan with classical connotations is naturally assumed. The main purpose of this article is to shed new light on the reasons for such changeover. It therefore proposes to recreate the hypothetical creative process of the architect, by re-drafting the different versions of the design, searching to reveal the key episodes within the decision-making process, such as the debate established between Kahn and Colin Rowe following the latter’s visit to Philadelphia, which may have prompted a radical change in the proposed arrangement model.